Antioxidant, anti-inflammatory and immunomodulatory effects of spirulina in exercise and sport: A systematic review - Calella, Patrizia; Cerullo, Giuseppe; Di Dio, Mirella; Liguori, Fabrizio; Di Onofrio, Valeria; Gallè, Francesca; Liguori, Giorgio (Frontiers in Nutrition, 2022)
Arthrospira platensis, also known as spirulina, is currently one of the most well-known algae supplements, mainly due to its high content of bioactive compounds that may promote human health. Some authors have hypothesized that spirulina consumption could protect subjects from exercise-induced oxidative stress, accelerate recovery by reducing muscle damage, and stimulate the immune system. Based on this, the main goal of this review was to critically analyze the effects of spirulina on oxidative stress, immune system, inflammation and performance in athletes and people undergoing exercise interventions. Of the 981 articles found, 428 studies were considered eligible and 13 met the established criteria and were included in this systematic review. Most recently spirulina supplementation has demonstrated ergogenic potential during submaximal exercise, increasing oxygen uptake and improving exercise tolerance. Nevertheless, spirulina supplementation does not seem to enhance physical performance in power athletes. Considering that data supporting benefits to the immune system from spirulina supplementation is still lacking, overall evidence regarding the benefit of spirulina supplementation in healthy people engaged in physical exercise is scarce and not consistent. Currently, spirulina supplementation might be considered in athletes who do not meet the recommended dietary intake of antioxidants. Further high-quality research is needed to evaluate the effects of spirulina consumption on performance, the immune system and recovery in athletes and active people.